Are CMV-predictive scores in inflammatory bowel disease useful in clinical practice? - Störkmann, Hedwig; Rödel, Jürgen; Stallmach, Andreas; Reuken, Philipp A. (Journal of Economic Literature, 2020)
Scoring systems can help to identify patients at risk for a CMV infection and minimize resource consumption and delay in treatment. Due to low incidence, a 2-step-algorithm, consisting of the Münster Score followed by a CMV-PCR if the score indicates a CMV infection, is preferable.